On the Involvement of BDNF Signaling in Memory Reconsolidation - Gonzalez, Maria Carolina; Radiske, Andressa; Cammarota, Martín (Frontiers in Cellular Neuroscience, 2019)
When retrieval occurs concomitantly with novelty detection, mismatch perception or reactivation of conflicting information, consolidated memories can enter into a labile state and, to persist, must be restabilized through a protein synthesis-dependent reconsolidation process during which their strength and content can be modified. Extensive literature implicates brain-derived neurotrophic factor (BDNF), a key regulator of synaptogenesis and synaptic plasticity, in the acquisition, consolidation and extinction of several memory types. However, the participation of BDNF in memory reconsolidation has been less studied. In this review, we discuss recent reports supporting the involvement of BDNF signaling in reactivation-induced memory updating.